Clay Mask Formulation of Coconut Dregs and Virgin Coconut Oil as an Antibacterial Against Propionibacterium acnes - Ketrin Evelia Pinondang Sitanggang; Ningsih Prastika Zega; Wulan Anggreni Br. Manurung; Elya Cytra Bonaparti Silaban; Helen Anjelina Simanjuntak (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Beauty and healthy skin as well as skin problems such as acne are challenges for the pharmaceutical sector in innovating to produce clay mask cosmetic products made from coconut dregs. Apart from maintaining healthy skin, coconut dregs clay mask products also maintain environmental health. Galactomannan contained in coconut dregs acts as a thickener, stabilizer, emulsifier and additive. The lauric acid contained in VCO acts as an antibacterial, antiviral and antiprotozoal. The combination of coconut dregs and VCO in a clay mask is more optimal as a cosmetic product. The aim of the research is to utilize coconut dregs waste into pharmaceutical products, produce a clay mask made from coconut dregs with a combination of VCO which has the potential to act as an antibacterial and produce a clay mask product that is effective as an anti-acne. The method was carried out by preparing coconut dregs flour, making various clay mask formulations: F0, F1, F2, F3 and F4, testing the stability of the clay mask product and testing the antibacterial properties of the clay mask against P. acnes using the well diffusion method. The results show that the organoleptic formulas are semi-solid, the colors are white, cream, brownish cream and light brown, while the odor ranges from odorless to vanilla, all formulas are homogeneous, pH 7, spreadability and dryness are stable and antibacterial is in the medium to strong category. The conclusion shows that F4 is more effective as an antibacterial against Propionibacterium acnes with an inhibition zone of 16.21 ± 0.85 mm and the clay mask preparation has the potential as an anti-acne